Transceiver and system design for digital communications - Bullock, Scott R. 1950- (SciTech Publishing, 2009)
The book covers the following topics: transceiver design; transmitter; receiver; AGC design and PLL comparison; demodulation; basic probability and pulse theory; multipath; improving the system against jammers; global navigation satellite systems; satellite communications; broadband communications and networking; and direction finding and interferometer analysis.